Replit: a simple approach to real-time collaborative coding / Adeline Engkamat, Yii Ming Leong and Shirley Sinatra Gran - Engkamat, Adeline; Yii, Ming Leong; Sinatra Gran, Shirley (Universiti Teknologi MARA, Kedah, 2023)
The current development of the tertiary education landscape sees the transformation where universities are shifting to a new norm, online and hybrid learning. As such, computer programming courses face challenges in offering interactive teaching and learning in these new environments, as computer programming courses require considerable hands-on coding practice, which is crucial for reinforcing the acquisition of programming concepts and skills. However, traditional online pedagogical tools like video lectures, reading material, and online quizzes fall short of what's needed for effective programming education. To acquire coding skills, it is imperative that students are provided with the opportunity to engage in practical coding exercises and remote collaboration with peers on actual coding tasks. As a result, Replit enters the picture. Replit is a free, browser-based coding platform that allows lecturers and students to collaborate on writing, reviewing, debugging, and sharing real-time coding projects. A study on the usefulness of Replit in learning programming subjects was conducted among Diploma in Computer Science students from Universiti Teknologi MARA Sarawak Branch. The results of the study showed that students have largely praised Replit for its accessibility, interactivity, and ability to facilitate group coding projects. Thus, this further proved that Replit helps to improve engagement between students and lecturers in programming subjects. Using Replit also encourages a collaborative learning environment and increases student participation in programming courses.